The mechanics of jumping over an obstacle during running: a comparison between athletes trained to hurdling and recreational runners - Mauroy, G.; Schepens, B.; Willems, P. A. (European Journal of Applied Physiology, 2014)
Purpose This study compares the mechanism of running in trained athletes (TA) experienced in hurdling and in recreational runners (RR), as they approach and jump over an obstacle. Methods The movements of the centre of mass of the body (COM), the external muscular work (W ext) and the leg-spring stiffness (k leg) were evaluated in athletes approaching an obstacle at 18 km/h, from the ground reaction forces (measured by force-platforms) and the orientation of the lower-limb segments (measured by camera). These results were compared to those obtained in RR. Results Two steps before the obstacle, k leg is reduced by 10-20 %; so, the COM is lowered and accelerated forward. During the step preceding the obstacle, k leg is increased by 40-60 %; so the COM is raised and accelerated upwards, whereas its forward velocity is reduced. This change in the running pattern is similar to the one observed in RR while leaping an obstacle. However, in TA, the change in stiffness is less pronounced. As a result, the orientation of the velocity vector at the beginning of the aerial phase over the obstacle is more horizontal than in RR, which involves a 10-20 % greater horizontal velocity and a 40-60 % smaller vertical excursion of the COM when crossing the obstacle; subsequently, W ext during contact before the obstacle is 10-20 % less. Conclusion Athletes use the same mechanisms as non-specialists to cross an obstacle. However, athletes adapt the mechanism of jumping to reduce the loss in the velocity of progression when crossing an obstacle.